Ultrasensitive and selective non-enzymatic electrochemical glucose sensor based on hybrid material of graphene nanosheets/graphene nanoribbons/nickel nanoparticle. (February 2018) - Jothi, L.; Jayakumar, N.; Jaganathan, S.K.; Nageswaran, G.
Graphical abstract: Highlights: Nickel nanoparticles incorporated graphene nanosheets/graphene nanoribbons (GS/GNR/Ni) composite was synthesized by in-situ chemical reduction route and the as prepared GS/GNR/Ni modified glassy carbon electrode (GCE) was applied to detect glucose. The fabricated GS/GNR/Ni/GCE modified electrode exhibits outstanding performance for non-enzymatic glucose sensing with sensitivity (2.3 mA/mM cm 2 ), linear range (5 nM - 5 mM) and detection limit (2.5 nM). GS/GNR/Ni/GCE modified electrode exhibited a high selectivity towards glucose against the interferents, such as ascorbic acid (AA), uric acid (UA), dopamine and sucrose. Abstract: A fast, highly sensitive and selective non-enzymatic electrochemical glucose sensor based on graphene sheet/graphene nanoribbon/nickel nanoparticles (GS/GNR/Ni) hybrid material modified electrode was fabricated. The hybrid material was synthesized via facile in-situ chemical reduction and characterized by X-ray diffraction, transmission electron microscopy, Raman spectroscopy, cyclic voltammetry and electrochemical impedance spectroscopy. The GS/GNR/Ni/GCE showed high electrochemical activity towards the oxidation of glucose in a 0.1 M NaOH solution. At an applied potential of +0.5 V, it displayed wide linear amperometric response towards glucose from the range of 5 nM–5 mM, with a detection limit of 2.5 nM and sensitivity of 2.3 mA/mM cm 2 . Moreover, the modified electrode was relatively insensitive to commonly interfering species such as dopamine, ascorbic acid, sucrose, uric acid and Cl − ions. The fabricated sensor with better reproducibility, good long term stability, makes it a promising electrode for the development of effective glucose sensor.